AKULTURASI PANCA INDRA METODE YADAIN LI TAHFIZIL QUR’AN - Yamin, Mochammad Ashabul; Astutik, Anita Puji (Faculty of Ushuluddin and Religious Studies UIN Sulthan Thaha Saifuddin Jambi, 2021)
The law of maintaining the purity of the Qur'an for all Muslims is fardhu 'ain (mandatory) for Muslims to maintain the authenticity of the contents and lafal of the Qur'an, either by studying, memorizing, thinking and studying the interpretation of the Qur'an. However, many people are afraid of memorizing the Qur'an because the language of the Qur'an is a foreign language and there are many and many verses in common, and what is no less important is the method of memorizing the Qur'an. They don't know yet, how to memorize the Qur'an easily, happily while still paying attention to the reading in accordance with the rules of ulumut tajwid while still paying attention to the tadabur side of the Qur'an when interacting with the Qur'an, either by memorizing or memorizing. Slowly, as time progressed, the methods of memorizing the Qur'an were perfected so that the Tahfiz al-Qur'an Quarantine Foundation formulated a sophisticated acceleration method that was given to Muslims who were able to answer the needs of the community if they wanted to memorize the Qur'an, namely memorizing the Qur'an using the Yadain Method by using the potential that exists within the five senses, which if in the process of memorizing it is done well with ‘ulum al-tajwid, it will make the process of memorizing the Qur'an easy. In this study, the author uses a qualitative approach which the author is directly involved in the field has applied the yadain method. The benefit in the application of this yadain method is to print a memorizer of the Qur'an by knowing the location of the verse and the number of the verse or what can be called (visualization of the Qur'an), then having the ability to memorize what is in the contents of the verses of the Qur'an. So that the messages contained in the Qur'an can reach him through contemplation of the verses of the Qur'an with the assistance of the translation of the Ministry of Religion of the Republic of Indonesia. Hukum menjaga kemurnian al-Qur’an bagi semua muslim ialah fardhu ‘ain (wajib) bagi para pemeluk Islam untuk menjaga keotentikan isi dan lafal al-Qur’an, baik dengan mempelajari, menghafal, mentadaburi dan mempelajari tafsir al-Qur’an. Akan tetapi banyak di antara masyarakat yang takut menghafal al-Qur'an dikarenakan bahasa al-Qur'an merupakan bahasa asing dan jumlahnya yang banyak serta mempunyai banyak kesamaan ayat, dan juga yang tidak kalah penting ialah metode dalam menghafal al-Qur’an pun mereka belum ketahui, bagaimana cara menghafal al-Qur’an dengan mudah, dengan bahagia yang tetap mengindahkan bacaan sesuai dengan kaidah ‘ulum al-tajwid beserta tetap memperhatikan sisi tadabbur al-Qur’an sewaktu berinteraksi dengan Al-Qur’an, baik dengan menghafal ataupun memuraja‘ah. Perlahan waktu yang terus berjalan mengalami penyempurnaan metode-metode dalam menghafal al-Qur’an sehingga menjadikan Yayasan Karantina Tahfiz al-Qur’an merumuskan sebuah metode akselerasi yang mutakhir yang diberikan kepada umat Islam yang mampu menjawab kebutuhan masyarakat apabila hendak menghafal al-Qur’an, yaitu menghafal al-Qur’an Metode Yadain dengan menggunakan potensi yang ada dalam diri berupa panca indera, yang apabila dalam proses menghafalnya dilakukan dengan baik dengan dibekali ‘ulum al-tajwid maka akan menjadi mudah proses menghafal al-Qur’an tersebut. Dalam penelitian ini penulis menggunakan pendekatan kualitatif yang penulis secara langsung terlibat di lapangan telah menerapkan metode yadain. Manfaat dalam penerapan metode yadain ini ialah mencetak seorang penghafal al-Qur’an dengan mengetahui letak ayat dan nomor ayat atau yang bisa disebut (visualisasi al-Qur’an), kemudian mempunyai kemampuan mentadaburi apa yang berada dalam isi kandungan ayat al-Qur’an sehingga pesan-pesan yang berada dalam al-Qur’an tersebut dapat tersampai padanya melalui perenungan ayat al-Qur’an dengan dibantu terjemahan Kementerian Agama Republik Indonesia.